MEIOK21 regulates oocyte quantity and quality via modulating meiotic recombination. Issue 6 (20th May 2022) - Shang, Yongliang; Huang, Ju; Li, Weidong; Zhang, Yanan; Zhou, Xu; Shao, Qiqi; Tan, Taicong; Yin, Shen; Zhang, Liangran; Wang, Shunxin
Abstract: The reproductive life span of females is largely determined by the number and quality of oocytes. Previously, we identified MEIOK21 as a meiotic recombination regulator required for male fertility. Here, we characterize the important roles of MEIOK21 in regulating female meiosis and oocyte number and quality. MEIOK21 localizes at recombination sites as a component of recombination bridges in oogenesis like in spermatogenesis. Meiok21 −/− female mice show subfertility. Consistently, the size of the primordial follicle pool in Meiok21 −/− females is only ~40% of wild‐type females because a great number of oocytes with defects in meiotic recombination and/or synapsis are eliminated. Furthermore, the numbers of primordial and growing follicles show a more marked decrease in an age‐dependent manner compared with wild‐type females. Further analysis shows Meiok21 −/− oocytes also have reduced rates of germinal vesicle breakdown and the first polar body extrusion when cultured in vitro, indicating poor oocyte quality. Additionally, Meiok21 −/− oocytes have more chromosomes bearing a single distally localized crossover (chiasmata), suggesting a possible defect in crossover maturation. Taken together, our findings indicate critical roles for MEIOK21 in ensuring the number and quality of oocytes in the follicles.